2017
DOI: 10.1007/s10546-017-0258-x
|View full text |Cite
|
Sign up to set email alerts
|

Are Urban-Canopy Velocity Profiles Exponential?

Abstract: Using analyses of data from extant direct numerical simulations and large-eddy simulations of boundary-layer and channel flows over and within urban-type canopies, sectional drag forces, Reynolds and dispersive shear stresses are examined for a range of roughness densities. Using the spatially-averaged mean velocity profiles these quantities allow deduction of the canopy mixing length and sectional drag coefficient. It is shown that the common assumptions about the behaviour of these quantities, needed to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 35 publications
(81 reference statements)
2
37
1
Order By: Relevance
“…In CB04 it was considered that the mixing length is proportional to the distance from the surface within a sparse canopy but is constant within a dense canopy. By combining the characteristics of both canopies, CB04 represented the mixing length, denoted here as l m, CB , as follows: validating the present LES, the profile of l m, eff in V00 is compared with the DNS result of Branford et al (2011) and Castro (2017), and seems to correspond well with the DNS result. Above the canopy, the profiles of l m, CB in all the simulations agree with those of l m, eff at and around the canopy top, while l m, CB gradually deviates from l m, eff as the height increases.…”
Section: Analysis Procedures For Mixing Lengthmentioning
confidence: 77%
See 3 more Smart Citations
“…In CB04 it was considered that the mixing length is proportional to the distance from the surface within a sparse canopy but is constant within a dense canopy. By combining the characteristics of both canopies, CB04 represented the mixing length, denoted here as l m, CB , as follows: validating the present LES, the profile of l m, eff in V00 is compared with the DNS result of Branford et al (2011) and Castro (2017), and seems to correspond well with the DNS result. Above the canopy, the profiles of l m, CB in all the simulations agree with those of l m, eff at and around the canopy top, while l m, CB gradually deviates from l m, eff as the height increases.…”
Section: Analysis Procedures For Mixing Lengthmentioning
confidence: 77%
“…In their studies, l m increases monotonically with height within the urban canopy as well as above the canopy top. In contrast, Castro (2017) showed that l m obtained from direct numerical simulation (DNS) and large-eddy simulation (LES) of flows over roughness obstacles with uniform height has a single local maximum within the canopy, and that l m has multiple local maxima within the canopy for flows over roughness with variable height. In this way, there are still unknowns on how and why the characteristics of l m appear depending on the urban geometrical feature.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The mixed-layer model only takes the mean boundary-layer wind into account, hence no vertical profiles of the wind can be modelled. In reality the boundary layer can experience vertical wind shear during neutral and weakly unstable conditions, especially in the complex terrain of cities [39][40][41], and knowledge of the vertical structure of wind speed is important for applications such as urban planning (e.g. through mechanical loads on buildings).…”
Section: Model Choicementioning
confidence: 99%